2021
DOI: 10.1101/2021.09.27.461956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecological stochasticity and phage induction diversify bacterioplankton communities at the microscale

Abstract: In many natural environments, microorganisms self-assemble around heterogeneously distributed resource patches. The growth and collapse of populations on resource patches can unfold within spatial ranges of a few hundred micrometers or less, making such microscale ecosystems hotspots of biological interactions and nutrient fluxes. Despite the potential importance of patch-level dynamics for the large-scale evolution and function of microbial communities, we have not yet been able to delineate the ecological pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…Bižić- Ionescu et al (2018) have shown, using the same system, that microbial succession on organic matter particles are initially driven by stochasticity and antagonistic interactions, rather than a change in carbon quality. Szabo et al (2021), though still using a closed experimental system, revealed as well a high heterogeneity in colonizers of homogenous artificial particles, reaching similar conclusions as Bižić- Ionescu et al (2018). These phenomena would not have been identified by analyzing bulk samples.…”
Section: Shifting Paradigmsupporting
confidence: 84%
See 1 more Smart Citation
“…Bižić- Ionescu et al (2018) have shown, using the same system, that microbial succession on organic matter particles are initially driven by stochasticity and antagonistic interactions, rather than a change in carbon quality. Szabo et al (2021), though still using a closed experimental system, revealed as well a high heterogeneity in colonizers of homogenous artificial particles, reaching similar conclusions as Bižić- Ionescu et al (2018). These phenomena would not have been identified by analyzing bulk samples.…”
Section: Shifting Paradigmsupporting
confidence: 84%
“…Nevertheless, to date there are only a handful of studies focusing on individual particles. Among these few have measured activity of individual particles ( Ploug 2001;Ionescu et al 2015;Belcher et al 2016;Stief et al 2021;Karthäuser et al 2021), and few have obtained sequencing data (Bižić-Ionescu et al 2018;Zäncker et al 2019;Szabo et al 2021;Vaksmaa et al 2022). Yet to the best of our knowledge no study has been published yet, combining both.…”
Section: Shifting Paradigmmentioning
confidence: 99%
“…Understanding what are the main drivers, or "ecological forces", shaping the coexistence and stability of microbial communities under changing environmental conditions and perturbations is a fundamental challenge of utmost relevance for, e.g., environmental and health sciences.Ecological forces can emerge from the interactions between species or between species and the environment, including both biotic and abiotic factors. Experiments in simple and controlled laboratory environments have made it possible to trace the effects of various ecological forces on community composition, often reshaping classical ideas on ecological interactions [3][4][5][6][7][8]. For instance, cross-feeding has emerged as a central player in determining community assembly and species coexistence [9,10].…”
mentioning
confidence: 99%
“…Our observation of prophage induction in cellulose degraders is consistent with a recent study of chitin-degrading marine microbial communities, in which prophages were found to be highly induced during biodegradation. 34 These findings underscore the importance of predatory interactions and biomass turnover, as fast-growing communities can also die faster, facilitating the transfer of carbon between different community members. 34,50 Although the molecular mechanisms that trigger phage induction are unknown and can be varied, our data suggests that prophage induction is a function of the amount of energy available for growth, as drastic death phases are only observed in fast growing communities.…”
Section: Environmentalmentioning
confidence: 92%
“…To test the viability of this hypothesis, we identified prophages in degrader MAGs and compare the coverage of prophage contigs and bacterial contigs within the same MAG. 34,35 Interestingly, we identify two phage contigs in the MAG of Cytophaga hutchinsonii. In all three samples of unmodified cellulose, the average coverage of the phage contig is significantly higher than that of bacterial contigs (Mann− Whitney test P = 2 × 10 −5 ), indicating a high level of prophage induction occurring in this cellulose degrader (Figure 4E, top three panels).…”
Section: Side Chain Modificationsmentioning
confidence: 94%